2018
DOI: 10.7717/peerj.5227
|View full text |Cite
|
Sign up to set email alerts
|

Investigating parental care behaviour in same-sex pairing of zoo greater flamingo (Phoenicopterus roseus)

Abstract: Same-sex pair bonds have been documented in several animal species and they are widespread in birds. However, little is known about the evolutionary origin and the adaptive value of such behaviour. The aim of this study was to investigate the parental behaviour of four zoo female greater flamingos involved in two breeding pairs, housed in a flock at Parco Natura Viva, Italy. Further, the behaviour of the study females was compared with that of male and female flamingos in heterosexual pairs described in a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…A single-case design was performed to analyse behavioural data of wildcats, using the total duration of each session calculated for each subject as dataset [46,47]. Nonparametric statistical tests were used to compare behavioural data of wildcats between and within periods.…”
Section: Discussionmentioning
confidence: 99%
“…A single-case design was performed to analyse behavioural data of wildcats, using the total duration of each session calculated for each subject as dataset [46,47]. Nonparametric statistical tests were used to compare behavioural data of wildcats between and within periods.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that ancestral behavioral plasticity played an essential role in the evolution of SSB in termites. The importance of sex-role plasticity in SSB is likely to be widely relevant because expression of behaviors associated with the other sex is frequently observed in other taxa (9,10). Therefore, our results have implications for understanding the nearly ubiquitous evolutionary maintenance of SSB across sexually reproducing animal taxa (1-4).…”
Section: Discussionmentioning
confidence: 84%
“…SSB is often more than misdirected behavior otherwise expressed during heterosexual encounters. In many species, sexual interactions between same-sex partners involve at least one partner expressing behaviors associated with the other sex, such as mimicking the other sex (9) or expressing the other sex's role during pair bonding (10), and evidence is emerging that SSB can involve distinct behavioral repertoires with separate neurological causation (11). The sex of the partner in a same-sex pairing is different from that in a heterosexual pairing, so plastic responses to different sociosexual environments should be essential for the expression of SSB.…”
mentioning
confidence: 99%
“…e . interacting partners being courted, mounted, paired, or receiving a copulation attempt) is often lacking, and as a result, it is underappreciated that both individuals may modify their behaviour during SSB to maintain same-sex pairing [40]. In this study, we empirically demonstrated that one of the partners in a same-sex pairing of termites flexibly expresses the behaviour of the other sex to contribute to pair coordination.…”
Section: Discussionmentioning
confidence: 86%